Explaining Positive Deviance in Public Sector Reforms in Development. (October 2015) - Andrews, Matt
Highlights: Public sector reforms are common in developing countries. Reforms commonly have limited results. There are cases of positive deviance, however, with surprisingly positive results. Most positive deviants emerge through problem driven, iterative adaptation (PDIA). Some positive deviants emerge from top down solution- and leader-driven change (SLDC). Summary: Public sector reforms are commonplace in developing countries. Much of the literature about these reforms reflects on their failures. This paper asks about the successes and investigates which of two competing theories best explain why some reforms are positive deviants: "solution- and leader-driven change" (SLDC) and "problem-driven iterative adaptation" (PDIA). The theories are used to analyze data emerging from a case survey involving thirty cases from Princeton University's Innovations for Successful Society (ISS) program. The bulk of evidence from this study supports a PDIA explanation, but there is reason to believe that SLDC hypotheses also have value.